(untitled) (Journal of Research Updates in Polymer Science, 2021)
The presented work shows the synthesis and characterization of Zn/Ti layered double hydroxide (LDH) intercalated with carbonate and dodecyl sulfate ions following its application as a functional filler in LDPE in order to improve the thermal properties and resistance degradation in UV-Vis radiation. X-ray diffractogram patterns of Zn/Ti LDH-CO3 and Zn/Ti LDH-DDS present basal spacing value in the order of 6.81 Å and 38.09 Å, respectively, indicating success in layered compound synthesis. LDPE nanocomposite containing hydrophobic and hydrophilic LDH presented a very well dispersed nanocomposite, as demonstrated in XRD and DSC results. The addition of only 1 % of LDH as filler into LDPE causes an increase of 5.43 oC in the thermal property. Zn/Ti LDH-DDS absorbs more light compared to the Zn/Ti LDH-CO3 due to the enhanced interlayer distance in the presence of DDS in the basal space of LDH, which further the intercalation process of polymer chains within the interlayer regions of LDH.